PLANNING CITIES BASED ON GENDER EQUALITY PRINCIPLES: APPROACHES AND EXPERIENCES - PROVOTAR, Nataliia; KOTSIUBA, Yaroslav (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. Integration of gender mainstreaming into urban planning is essential for achieving social justice, inclusiveness, and  sustainable urban development. Implementing gender equality principles in urban planning enhances the quality of life for all residents. Experiences  from cities worldwide demonstrate the effectiveness and necessity of adopting gender-sensitive approaches to urban planning. The aim of the study  is to explore approaches and positive experiences in city planning based on gender equality, as well as to identify the advantages, challenges, and  opportunities for their application in Ukrainian cities. Methods. The study draws on diverse sources, including scientific research (articles and monographs), materials and projects from  international organisations, presentations, discussions of initiatives, and expert commentary in the field of urban planning. The results were obtained  using methods of analysis and synthesis, the construction of logical schemes, and SWOT analysis. Results. This article presents the results of a study analysing positive examples of gender mainstreaming projects of varying scales in cities  across the globe. It identifies practices that can be adapted for implementation in Ukraine while outlining the challenges and opportunities associated  with urban planning in the context of gender mainstreaming. A logical framework was developed to conceptualise gender mainstreaming within the  context of creating a gender-just city. The research highlights that integrating gender perspectives into urban planning significantly enhances the  functionality, inclusiveness, safety, accessibility, and comfort of urban spaces for all citizens. To further explore these opportunities, a SWOT analysis  was conducted to identify the strengths, weaknesses, opportunities, and threats associated with implementing gender-sensitive approaches in  Ukraine's urban planning processes.  Сonclusions. Successful gender-sensitive planning projects demonstrate that addressing the needs of diverse social groups not only  improves the comfort of the urban environment but also fosters social integration. These projects can serve as models for Ukrainian cities, offering  valuable insights for adaptation to local contexts. The findings provide a foundation for developing inclusive and sustainable cities while  strengthening citizen participation in urban planning and governance.
Keywords: city; gender equality; gender mainstreaming; public spaces; urban planning; participation